Achieving good‐quality consent: review of literature, case law and guidance. Issue 5 (31st May 2020) - Normahani, P.; Sounderajah, V.; Harrop‐Griffiths, W.; Chukwuemeka, A.; Peters, N. S.; Standfield, N. J.; Collins, M.; Jaffer, U.
Abstract : Background: Informed consent is an integral part of clinical practice. There is widespread agreement amongst health professionals that obtaining procedural consent needs to move away from a unidirectional transfer of information to a process of supporting patients in making informed, self‐determined decisions. This review aimed to identify processes and measures that warrant consideration when engaging in consent‐based discussions with competent patients undergoing elective procedures. Methods: Formal written guidance from the General Medical Council and Royal College of Surgeons of England, in addition to peer‐reviewed literature and case law, was considered in the formulation of this review. Results: A framework for obtaining consent is presented that is informed by the key tenets of shared decision‐making (SDM), a model that advocates the contribution of both the clinician and patient to the decision‐making process through emphasis on patient participation, analysis of empirical evidence, and effective information exchange. Moreover, areas of contention are highlighted in which further guidance and research are necessary for improved enhancement of the consent process. Conclusion: This SDM‐centric framework provides structure, detail and suggestions for achieving meaningful consent. Abstract : This review aimed to identify processes and measures that warrant consideration when engaging in consent‐based discussions with competent patients undergoing elective procedures. A strategy for shared decision‐making Abstract : Antecedentes: El consentimiento informado es una parte integral de la práctica clínica. Existe un acuerdo generalizado entre los profesionales de la salud en que lograr el consentimiento del procedimiento no debe ser una transferencia unidireccional de información, sino un proceso de apoyo a los pacientes en la toma de decisiones informadas y autodeterminadas. Esta revisión tiene como objetivo identificar procesos y medidas que deban ser considerados al hablar sobre el consentimiento con pacientes autosuficientes sometidos a procedimientos quirúrgicos electivos. Métodos: Al planear esta revisión se tuvo en cuenta la recomendación formal por escrito del Consejo Médico General y del Royal College of Surgeons of England, además de la literatura revisada por pares y de la jurisprudencia. Resultados: Se presenta un marco para lograr el consentimiento que se basa en los principios clave de la toma de decisiones compartida ( Shared Decision‐Making, SDM); un modelo que aboga por la contribución, tanto del médico como del paciente, al proceso de toma de decisiones a través del énfasis en la participación del paciente, el análisis de la evidencia empírica y el intercambio efectivo de información. Además, se destacan áreas de contención en las que se necesitan más recomendaciones y más investigación para mejorar aún más el proceso del consentimiento. Conclusión: Este marco centrado en la SDM proporciona estructura, detalles y sugerencias sobre cómo se puede lograr un consentimiento informado satisfactorio.